Respuesta :

Answer:

[tex](rs)(4) = 8[/tex]

Step-by-step explanation:

Given

[tex]r(x) = 2\sqrt{x[/tex]

[tex]s(x) = \sqrt x[/tex]

Required

Determine [tex](rs)(4)[/tex]

In functions:

[tex](fg)(x) = f(x) * g(x)[/tex]

This implies that:

[tex](rs)(x) = r(x) * s(x)[/tex]

Substitute values for r(x) and s(x)

[tex](rs)(x) = 2\sqrt{x} * \sqrt{x}[/tex]

[tex](rs)(x) = 2(\sqrt{x})^2[/tex]

[tex](rs)(x) = 2x[/tex]

Substitute 4 for x

[tex](rs)(4) = 2 * 4[/tex]

[tex](rs)(4) = 8[/tex]

Otras preguntas